ON HEARING COLOURS – CROSS-MODAL ASSOCIATIONS IN VOWEL PERCEPTION IN A NON-SYNAESTHETIC POPULATION - Wrembel, Magdalena (Versita Ltd., de Gruyter, 2009)
The present study is a continuation of previous investigations into the nature of sound−colour as- sociations in a non-synaesthetic population conducted on English and Polish vowel sound sys- tems and it aims at providing further evidence for the non-arbitrary nature of cross-modal map- pings. The experiment1 was run on a specially designed computer program and involved 90 par- ticipants who were asked to match randomised auditory stimuli (12 English vowel sounds re- corded in 2 conditions: in isolation and in a CVC context) with one of 11 basic colours (red, yel- low, green, blue, brown, purple, pink, orange, black, white and grey) presented as coloured rec- tangles on a computer screen. The program kept record of the colour choice and reaction time of the participants, who fell into 2 groups with respect to the level of their language proficiency and phonetic awareness. An analysis of the results revealed statistically significant interactions between specific col- ours and individual vowel sounds for all 12 English vowels examined in the combined analysis; for 10 vowels in Condition 1 (isolated auditory stimuli) and for 7 vowels in Condition 2 (stimuli in the CVC context). A group effect was not found to be significant as far as the quality of map- pings was concerned; however, in the case of reaction times the less advanced learners took sig- nificantly longer to assign colours to sounds in context. The findings indicate that vowel−sound mappings in non-synaesthetic perception appear non-arbitrary and follow the general tendencies in which bright colours (yellow, green) are associated with high front vowel sounds, whereas dark colours (brown, blue, black) are attributed to back vowels, while open sounds tend to be perceived as red and central vowels are mapped onto achromatic grey.
Keywords: Sound−colour mappings; vowel colour; synaesthesia